Reduction of Soot Emission from Diesel Fuel Engine Using a Novel Diesel Particulate Filter - Mohd Taib, Mohsein (2009)
Malaysia is a rapidly developing country that is working hard towards achieving its Vision 2020, of becoming a developed country. The increase in economic activities has also resulted to an increase in the country air pollution problem. One of the main sources of the pollutants is emissions from motor vehicles, which is originated from incomplete fuel combustion; either diesel or gasoline. Among the emissions that are considered to be harmful to human health and environment are carbon monoxide (CO), hydrocarbon (HC), nitrogen oxide (NOX), sulphur oxide (SOX) and carbon soot. Most emissions are equally contributed both gasoline and diesel fuelled vehicles. However, heavy duty diesel fuelled vehicles are the main contributor for the soot and NOX emissions. At present, in Malaysia, there is no regulation that forces diesel fuelled vehicles to be installed with exhaust after treatment system, which is able to reduce soot emission. In this paper, an overview on the control of emissions from diesel fuelled vehicles in Malaysia will be presented. In addition to that, description of a novel exhaust after treatment system, based on porous medium, which aims to suppress soot emission from diesel fuelled vehicles, is also be included.